Assessment of the Prevalence of the Use of Nasal Decongestants Among Hail Population - Farida Habib Khan; Abdullah D Alotaibi; Amal Daher Alshammari; Mohammed Alateeq; Muath Alshmmari; Read Alharbi; Rakhi Issrani (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Nasal decongestants are widely used to relieve nasal congestion caused by conditions such as allergic rhinitis, sinusitis, and the common cold. These medications function by constricting nasal blood vessels, reducing swelling, and improving airflow. Despite their effectiveness, improper use can result in adverse effects, including rebound congestion and cardiovascular complications. Materials and Methods: A cross-sectional study was conducted among 300 adult residents of Hail, Saudi Arabia, using a structured questionnaire. Participants were selected through simple random sampling. The questionnaire assessed the frequency of nasal decongestant use, types of decongestants preferred, reasons for use, and awareness regarding potential health risks. Data were analyzed using descriptive statistics, and Chi-square tests were performed to evaluate associations between demographic factors and decongestant use. Results: Among the participants, 65% reported regular nasal decongestant use, with 45% preferring topical decongestants (e.g., oxymetazoline) and 55% using oral formulations (e.g., pseudoephedrine). The majority (72%) reported self-medicating without medical consultation, while 60% were unaware of the risk of rebound congestion. Individuals with a history of allergic rhinitis or sinusitis were significantly more likely to use nasal decongestants frequently (P < 0.05). Additionally, 30% of users experienced side effects, including increased heart rate (15%) and nasal irritation (10%). Conclusion: The study highlights a high prevalence of nasal decongestant use in Hail, largely influenced by environmental factors and a lack of public awareness regarding potential risks. The findings underscore the need for targeted public health campaigns and pharmacist-led interventions to promote safer usage practices.